1986
DOI: 10.1002/jor.1100040112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulley excision on flexor tendon biomechanics

Abstract: Flexor tendon function following excision of various portions of the fibro-osseous pulley system was measured biomechanically using a tensile testing machine. The biomechanical parameters measured were tendon excursion (the excursion of the tendon required to fully flex the digit) and work of flexion (the area under the force-excursion curve, representing all the forces that resist tendon flexion). In this experiment, work of flexion included the forces necessary to accomplish full digital flexion against a 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 7 publications
1
56
0
2
Order By: Relevance
“…Scanning electron microscopy of the human A2 pulley shows the same transverse fiber direction, perpendicular to the forces applied by the tendons as in these animals, leading to a preferential direction for friction because the shape of the tendon and the direction of the fibers changed when the tendon was under tension (Walbeehm and McGrouther, 1995). Friction between pulleys and flexor tendons has been investigated in several studies in order to assess friction of different suture techniques and tendon grafts Nishida et al, 1998;Peterson et al, 1986;Uchiyama et al, 1997Uchiyama et al, , 1995Williams and Amis, 1995;Woo et al, 1981), but these studies focused on concentric movement. Schweizer et al (2003) developed a method for determining the effect of friction between human finger flexor tendons and pulleys in vivo during high load.…”
Section: Discussionmentioning
confidence: 98%
“…Scanning electron microscopy of the human A2 pulley shows the same transverse fiber direction, perpendicular to the forces applied by the tendons as in these animals, leading to a preferential direction for friction because the shape of the tendon and the direction of the fibers changed when the tendon was under tension (Walbeehm and McGrouther, 1995). Friction between pulleys and flexor tendons has been investigated in several studies in order to assess friction of different suture techniques and tendon grafts Nishida et al, 1998;Peterson et al, 1986;Uchiyama et al, 1997Uchiyama et al, , 1995Williams and Amis, 1995;Woo et al, 1981), but these studies focused on concentric movement. Schweizer et al (2003) developed a method for determining the effect of friction between human finger flexor tendons and pulleys in vivo during high load.…”
Section: Discussionmentioning
confidence: 98%
“…Here, its tip is seen transecting the A1 pulley. Note how the operator can ensure that it remains dead centre over the flexor tendon under sonographic guidance during the procedure, particularly the digital nerves which have been shown to have a variable course in cadaveric studies [12][13][14][15][16][17][18][19][20][21][22]. Several studies suggest the variation in digital nerve position in the thumb, index and little finger puts non-image-guided percutaneous release at risk of complications [6,8,12,16,20,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The "blind" percutaneous technique uses surface anatomical landmarks [12][13][14][15][16][17][18][19][20][21][22]. Although it has been shown to be safe, it is complicated by incomplete release or the need to convert to an open release, which has been reported in up to 11% of cases [13,16,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, biomechanical studies have shown the A2 pulley to be the most important for flexor tendon function, followed by A4. 55 Proximal partial pulley excision may have a greater effect on digit range of motion than distal partial pulley excision. 56 To avoid the sequelae of A2 resection, reduction flexor tenoplasty has been reported.…”
Section: Triggeringmentioning
confidence: 98%